Plasma Scalpels: Devices, Diagnostics, and Applications - Ao Xiao; Dawei Liu; Dongcheng He; Xinpei Lu; Kostya (Ken) Ostrikov (Biomedicines, 2022)
The plasma scalpel is an application of gas discharges in electrosurgery. This paper introduces the device structure and physicochemical parameters of the two types of plasma scalpels, namely, a single-electrode Ar discharge device (argon plasma coagulation) and a two-electrode discharge device in normal saline. The diagnostic methods, including the voltage and current characteristics, optical emission spectroscopy, electron spin resonance, and high-speed imaging, are introduced to determine the critical process parameters, such as the plasma power, the gas temperature, the electron density, and the density of active species, and study the ignition dynamics of the plasma discharges in water. The efficacy of the plasma scalpel is mainly based on the physical effects of the electric current and electric field, in addition to the chemical effects of high-density energetic electrons and reactive species. These two effects can be adjusted separately to increase the treatment efficacy of the plasma scalpel. Specific guidance on further improvements of the plasma scalpel devices is also provided.